2020
DOI: 10.1155/2020/1702695
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Injection with Conjunctival Microincision for the Treatment of Acute Acquired Comitant Esotropia and Its Effectiveness

Abstract: Purpose. To report on an improved botulinum toxin injection with conjunctival microincision for beginners, and to determine the effectiveness of botulinum toxin A (BTXA) in the treatment of patients with acute acquired comitant esotropia (AACE). Methods. Medical records of 29 AACE patients were retrospectively analyzed. BTXA was injected into the unilateral or bilateral medial rectus muscle with conjunctival microincision without electromyographic guidance. Success was defined as total horizontal deviation ≤10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…However, although the direct effect of botulinum toxin lasted only three months, its effect on eye position can last longer. 19 In Xu study, the effects lasted longer than six months, 17 and in our study, the deviation angle was smaller at six months than before treatment. This long-lasting effect may be beneficial to patients who refuse conventional surgery or general anesthesia.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, although the direct effect of botulinum toxin lasted only three months, its effect on eye position can last longer. 19 In Xu study, the effects lasted longer than six months, 17 and in our study, the deviation angle was smaller at six months than before treatment. This long-lasting effect may be beneficial to patients who refuse conventional surgery or general anesthesia.…”
Section: Discussionsupporting
confidence: 47%
“…A retrospective study by Xu et al 17 examined 29 AACE patients who received botulinum toxin injection to determine the treatment’s effectiveness. The dose of botulinum toxin used varied by preoperative deviation angle (5 IU, 6 IU, and 7 IU for deviation angles of 20–40 PD, 40–60 PD, and 60–80 PD, respectively), which resulted in a success rate of 86.2% at six months and 82.8% at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Dawson et al's [10] study revealed that timely BTXA injections within 8wk of onset resulted in favorable outcomes, with 80% of children remaining orthoptic and gradually establishing stereopsis. Similarly, Wan et al [11] reported an average onset-totreatment duration of 3mo, while Xu et al [42] observed a success rate of 82.8% at a 6-month follow-up, with onset-to-treatment ranging from 1 to 96wk. These findings collectively suggest that early BTXA application is practical in AACE treatment.…”
Section: Discussionmentioning
confidence: 90%
“…While there is no strict prohibition against attempting BTXA treatment for large-angle AACE, established norms and indications suggest its relatively positive efficacy in small to moderate deviations of comitant strabismus (<40 Δ ) [40] . Previous analyses have not analyzed the efficacy of a range of deviations in isolation, and subjects have often included small deviations as well as large angles of AACE [10][11][13][14][41][42] . Consequently, this study focuses on the clinically prevalent range of AACE with small deviations (≤25 Δ ).…”
Section: Discussionmentioning
confidence: 99%
“…Careful surgical planning and operation can prevent severe complications, including scleral perforations, orbital inflammation, muscle slip, and anesthesia complications (20). BTXA was also found to be a safe, effective, and repeatable treatment for AACE, with fewer iatrogenic injuries (10,17,21,22). Because of the individual response of BTXA (18), and limitations of the syringe scale, surgeons cannot precisely administer BTXA doses according to the deviation.…”
Section: Discussionmentioning
confidence: 99%